CT-Guided Aspiration of a Hemorrhagic Tarlov Cyst for the Treatment of a Post-Partum Sciatica: A Case Report and a Review of the Literature - Serratrice, Nicolas; Taifour, Sarkis; Attieh, Christian; Faddoul, Joe; Tarabay, Bilal; Yachou, Yassine; Chalah, Moussa A.; Ayache, Samar S.; Abi Lahoud, Georges Naïm (Frontiers in Surgery, 2022)
Background: Tarlov or perineural cysts are dilations of nerve roots resulting from a pathologically increased cerebrospinal fluid pressure. Although it is very common in the general population, most of these cysts remain asymptomatic. In some cases, they can evolve and exert pressure on neural elements, independently from their initial size. Case report: In this paper, we describe the case of a 33-year-old female known to have asymptomatic multiple and large radicular and pelvic Tarlov cysts. One cyst located in the right pelvic space progressed acutely after delivery, inducing a painful sciatica without neurological deficit. The intracystic bleeding can be a direct consequence of the delivery, leading to an acute and mechanical local compression of the right S1 root. A CT-guided puncture and aspiration allowed a complete recovery. This case report was completed by a review of the literature of these rare intracystic Tarlov bleedings. Conclusions: Intracystic hemorrhage is a rare complication of Tarlov cysts. Delivery-induced cyst bleeding was not described before. Patients known to have large and multiple Tarlov cysts should be monitored in post-partum, as their presence is considered a risk factor. Percutaneous cyst aspiration seems to be an effective and safe treatment to relieve symptoms.